Body position and cuff size influence lower limb arterial occlusion pressure and its predictors: implications for standardizing the pressure applied in training with blood flow restriction - de Queiros, Victor S.; Rolnick, Nicholas; Kamiş, Okan; Formiga, Magno F.; Rocha, Roberto F. C.; Alves, Júlio César Medeiros; Vieira, João Guilherme; Vianna, Jeferson Macedo; Wilk, Michal; Fostiak, Krzysztof; Cabral, Breno Guilherme de Araújo Tinôco; Dantas, Paulo Moreira Silva (Frontiers in Physiology, 2024)
Background: Arterial occlusion pressure (AOP) is a relevant measurement for individualized prescription of exercise with blood flow restriction (BFRE). Therefore, it is important to consider factors that may influence this measure. Purpose: This study aimed to compare lower limb AOP (LL-AOP) measured with 11 cm (medium) and 18 cm (large) cuffs, in different body positions, and explore the predictors for each of the LL-AOP measurements performed. This information may be useful for future studies that seek to develop approaches to improve the standardization of pressure adopted in BFRE, including proposals for equations to estimate LL-AOP. Methods: This is a cross-sectional study. Fiftyone healthy volunteers (males, n = 25, females, n = 26; Age: 18 to 40 years old) underwent measurement of thigh circumference (TC), brachial blood pressure, followed by assessments of LL-AOP with medium and large cuffs in positions supine, sitting and standing positions. Results: The large cuff required less external pressure (mmHg) to elicit arterial occlusion in all three-body positions when compared to the medium cuff (p<0.001). The LL-AOP was significantly lower in the supine position, regardless of the cuff used (p<0.001). Systolic blood pressure was the main predictor of LL-AOP in the large cuff, while TC was the main predictor of LL-AOP with the medium cuff. Body position influenced strength of the LL-AOP predictors. Conclusion: Our results indicate that LL-AOP and its predictors are substantially influenced by body position and cuff width. Therefore, these variables should be considered when standardizing the pressure prescribed in BFRE.